1990
DOI: 10.1073/pnas.87.23.9503
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic field around cytochrome c: theory and energy transfer experiment.

Abstract: Energy transfer in the "rapid diffusion" limit from electronically excited terbium(llI) chelates in three different charge states to horse heart ferricytochrome c was measured as a function of ionic strength. Theoretical rate constants calculated by numerical integration of the Forster integral (containing the Poisson-Boltzmann-generated protein electrostatic potential) were compared with the experimental data to evaluate the accuracy of protein electrostatic field calculations at the protein/solvent interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 18 publications
2
31
0
Order By: Relevance
“…From the spherical symmetry of e(r) it also appears that electrostatic interactions in proteins are not nearly as sensitive to shape as commonly thought. Moreover, the results obtained here are clearly in agreement with Northrup et al (1990), that the rigid molecule assumption seems to be reliable in most cases. The calculations presented here and previously, also show that in nearly all cases the SCP model yields results at least as reliable as those obtained from a numerical solution of the PB equation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…From the spherical symmetry of e(r) it also appears that electrostatic interactions in proteins are not nearly as sensitive to shape as commonly thought. Moreover, the results obtained here are clearly in agreement with Northrup et al (1990), that the rigid molecule assumption seems to be reliable in most cases. The calculations presented here and previously, also show that in nearly all cases the SCP model yields results at least as reliable as those obtained from a numerical solution of the PB equation.…”
Section: Discussionsupporting
confidence: 81%
“…This assumption implies that there are no major conformational changes in solution, which appears to be the case for most (but not all) proteins. A recent analysis by Northrup et al (1990) seems to support this assumption, although the authors also concluded that details of the electrostatic effects require a consideration of protein flexibility. Due to its simplicity, the SCP could be implemented in calculating the electrostatic component of the potential functions used in molecular mechanics and molecular dynamics simulations.…”
Section: Introductionmentioning
confidence: 82%
“…The involvement of charged residues in the specificity and stabilization of electrostatic complexes between a variety of electron transfer proteins is well documented (KostiS, 1991), though little is known about the pH dependence of these reactions. This deficiency is surprising because the electrostatic potential surface of a protein is defined by the protonation state of its constitutent titratable groups [for recent studies concerning this relationship, see Wendoloski and Matthew (1 989) and Northrup et al (1990)l. Although no detailed structural characterization of a complex formed by such proteins is available, much effort has gone into evaluating general features of model structures proposed on the basis of crystallographic information and electrostatic calculations concerning the individual components of the complex.…”
mentioning
confidence: 96%
“…2.3 and the work of Swanson et al [54,83]). For each method of computing φ (SRF) (FFT of the explicit-solvent charge density or FDMG using implicit solvent with a pre-defined, low dielectric solute volume inside a high-dielectric solvent region), the electrostatic energy of an atom i in φ (SRF) was calculated using (7) for explicit solvent reaction fields, with variants and for the charged and uncharged solute simulations, respectively. Likewise, for implicit solvent reaction fields, the electrostatic energy is defined as (8) with variants and for the charged and uncharged solute simulations, respectively.…”
Section: Relating the Explicit Solvent Reaction Field Potential To Immentioning
confidence: 99%
“…The electrostatic properties of solvated biomolecules are a subject of intense computational [1][2][3] as well as experimental interest [4][5][6][7]. The polar nature of water molecules influences the structure of proteins, nucleic acids, and lipid membranes.…”
Section: Introductionmentioning
confidence: 99%